Factor the polynomial and use the factored form to find the zeros. (Enter your a

Algebra
Tutor: None Selected Time limit: 1 Day

P(x) = x4 − 3x2 − 4
x = 
Mar 15th, 2015

P(x) = x^4 - 3x^2 - 4
= x^4 - 4x^2 +x^2 -4
= x^2 ( x^2 - 4)+1(x^2 - 4)
=(x^2 +1)(x^-4)
=(x^2 + 1)(x+2)(x-2)

to find the zeros,
(x^2+1)(x+2)(x-2) =0
x^2+1 = 0 or x+2 =0 or x -2=0
x^2 = -1 or x=-2 or x=2
x= sqrt(-1)= i or x =-2 or x =2

x = i, -2 and 2

Please best my answer if it was helpful to you.

Mar 15th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Mar 15th, 2015
...
Mar 15th, 2015
Dec 11th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer